2015
DOI: 10.1074/jbc.m114.577486
|View full text |Cite
|
Sign up to set email alerts
|

K+ Congeners That Do Not Compromise Na+ Activation of the Na+,K+-ATPase

Abstract: Background:The Na ϩ ,K ϩ -ATPase discriminates between similar and abundant ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…All-atom MD simulations were performed in a manner similar to one described in a recent publication 52 . The recently determined, crystal structure of the [Na 3 ] E1-AlF4-ADP form of pig kidney NaKA (PDB ID: 3WGU 4 ) was used as a starting point of the simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All-atom MD simulations were performed in a manner similar to one described in a recent publication 52 . The recently determined, crystal structure of the [Na 3 ] E1-AlF4-ADP form of pig kidney NaKA (PDB ID: 3WGU 4 ) was used as a starting point of the simulations.…”
Section: Methodsmentioning
confidence: 99%
“…System construction – The Na + coordinating residues E327 and E779 at binding sites I and II , as well as E954 at the unoccupied site IIIa were kept protonated 52 . The remaining glutamate and aspartate residues were kept in the charged state.…”
Section: Methodsmentioning
confidence: 99%
“…More than 40% of the energy produced in mammals is consumed by the Na + /K + -pump ( Milligan et al, 1985 ). Although it is a machine designed for such a precise and important function, it has been shown that many cations, including congeners of K + and some organic cations, can bind to the same sites used by the pump to bind and transport K + ions ( Mahmmoud et al, 2015 ; Ratheal et al, 2010 ). Competitive binding between Na + and other cations at the cytoplasmic side of the membrane has also been observed ( Schneeberger et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since too many water molecules inside the binding pocket can cause the hydration and destabilization of Na + ions1252, we consider a state with fewer waters around the bound Na + ions as a more stable one. Note that at least two water molecules accompany Na + in all simulations.…”
Section: Resultsmentioning
confidence: 99%